ULTRAVIOLET MICROSCOPY OF THE VACUOLE OF SACCHAROMYCES CEREVISIAE DURING SPORULATION - Svihla, G. (1964)
Svihla, G. (Argonne National Laboratory, Argonne, Ill.), J. L. Dainko, and F. Schlenk. Ultraviolet microscopy of the vacuole of Saccharomyces cerevisiae during sporulation. J. Bacteriol. 88:449–456. 1964.—Normal cells of Saccharomyces cerevisiae and cells containing, in their vacuoles, large quantities of S-adenosylmethionine were induced to sporulate. In the latter case, the strong ultraviolet absorption of the compound permitted photomicrographic observation of cytological detail. Chromatographic and spectrophotometric analyses of cell extracts supplemented the cytological studies. The vacuole is abolished at the onset of sporulation, and its contents may be observed temporarily in the intersporular space. As sporulation progresses, the material is discharged into the culture medium. Sporulation of both types of cells also leads to a release of nucleic acid fragments into the culture medium.